Kinerja Pelayanan Publik Studi Kasus Pada Dinas Kependudukan dan Catatan Sipil (Disdukcapil) Kota Jambi - Samsudin, Samsudin; Pribadi, Ulung (Journal of Governance and Public Policy, 2014)
The purpose of  this study is to determine the performance of public services in the Dinas Kependudukan dan CatatanSipil Kota Jambi. This study uses the concept of  performance measurement with five indicators of  productivity, qualityof  service, responsiveness, r esponsibility and accountability. These indica tors are used to measure  the efficiency andeffectiveness of  services, quality of  service received by  the public. The method used in this research is quantitativemethod. The research location is determined by the method of  purposive, are determined by deliberate that the studywas conducted in the Depar tment of P opulation and Civil Registry. Data  collection techniques used in this study includeinterviews, observations, and literature. Based on the research findings that the productivity of  public services interms of  the ability of  officers and service performance can be summed been efficient with an average result value of70% of  respondents said either. The quality of  service in terms of  satisfaction of  the performance of  services,timeliness of  service, comfortable environment and good infrastructure which is an average result of  41% while themeasured responsiveness of service delivery performance , kedesiplinan, service procedur es and speed of  service.The final result that  stands out from the responsiveness can be judged good quality with an average of 51% of  goodquality, the next responsibility is measured on the suitability of cost and fairness of  service delivery is good is seenfrom the average value of  responsibility is 45% and the accountability of  public service in the Department of  Popula-tion and Jambi City Civil Registry, is good  for 70% of  respondents  said that responsibility.